Dermoscopic diagnosis of ashy dermatosis: A retrospective study - Ömer Faruk Elmas; Emine Müge Acar; Asuman Kilitçi (Wolters Kluwer Medknow Publications, 2019)
Aim: Ashy dermatosis (AD) is a cutaneous pigmentation disorder with unknown etiology characterized by ash-colored hyperpigmented macules. The diagnosis of Ashy dermatosis is primarily based on the clinical and histopathological findings. In this study, we aimed to identify the dermoscopic features of AD, which may facilitate the diagnosis by reducing the need for invasive procedures. Material and Methods: The study included the patients diagnosed with Ashy dermatosis. Demographic, clinical, dermoscopic and histopathological features of the lesions were reviewed and the findings observed were recorded. Results: A total of 60 lesions from 15 patients were included. The most common dermoscopic finding were irregular linear dots and globules, pinkish brown color was the predominant color of the background, and found to be associated with early lesions. Among the vascular structures observed, irregular linear vessels were the most prevalent. There were no significant differences in terms of dermoscopic structures according to age and localization of the lesions. Conclusion: Dermoscopy can serve as a noninvasive helpful tool for the diagnosis of Ashy dermatosis.